Bone reporting and data system on CT (Bone-RADS-CT): a validation study by four readers on 328 cases from three local and two public databases - Yue Xing; Defang Ding; Shun Dai; Yangfan Hu; Xianwei Liu; Liangjing Lyu; Guangcheng Zhang; Shiqi Mao; Qian Yin; Junjie Lu; Jiarui Yang; Yang Song; et al. (Insights into Imaging)
Abstract Objective To evaluate the reproducibility and effectiveness of the bone reporting and data system on CT (Bone‐RADS-CT) for incidental solitary bone lesions in adults. Materials and methods We retrospectively included 328 CT cases from three local and two public databases, respectively. All the cases were histopathologically or clinically confirmed bone lesions, “do not touch” lesions with typical appearance, and remained stable for at least 2 years. Each lesion with gender, age, and clinical history was categorized according to the Bone-RADS algorithm by two musculoskeletal radiologists and two non-musculoskeletal radiologists. The Bone-RADS categories were as follows: Bone-RADS-1, likely benign, leave alone; Bone-RADS-2, incomplete assessed on imaging, perform different imaging modality; Bone-RADS-3, intermediate, perform follow-up imaging; Bone-RADS-4, suspicious for malignancy or need for treatment, biopsy and/or oncologic referral. Inter-reader agreement was evaluated. The diagnostic performance of the Bone-RADS-CT for distinguishing positive cases (intermediate or malignant lesions or osteomyelitis) from negative cases (benign lesions), were measured, using histopathology results, clinical diagnosis, or follow-up as a standard reference. Results There were 223 positive cases and 105 negative cases, respectively. The overall inter-reader agreement between two musculoskeletal and two non-musculoskeletal radiologists were both moderate (weighted kappa 0.553 and 0.403). The diagnostic performance for identifying intermediate or malignant lesions or osteomyelitis ranged according to radiologists with sensitivities of 88.8% to 94.6%, specificities of 42.9% to 71.1%, and accuracies of 78.0% to 86.6%. Conclusion Bone-RADS-CT is effective for identifying bone lesions that need further treatment, but is only moderately reliable for readers of different specialties and experience. Critical relevance statement Bone-RADS-CT has been demonstrated to be a reliable algorithm for non-musculoskeletal radiologists and an effective tool for identifying the “need for treatment” incidental solitary bone lesions in adults, but still needs improvement in the rating method and category definition. Key Points Bone-RADS-CT has been demonstrated to be reliable and accurate when rated by musculoskeletal radiologists. Bone-RADS-CT achieved moderate agreement for musculoskeletal and non-musculoskeletal radiologists. Bone-RADS-CT presented high sensitivities but low specificities for identifying “need for treatment” bone lesions. Graphical Abstract